The implementation of cryoconservation for rare species Dianthus gratianopolitanus Vill. (Caryophyllaceae) seeds conservation - E.R. Arapetyan; M.G. Mohyliak; J.M. Usatenko (Інтродукція Рослин, 2006)
The influence of cryoconservation in liquid hydrogen on laboratory germination and initial phases of ontogenesis of Dianthus gratianopolitanus Vill. seeds was observed.